Vulnerability of the Church through Abuse of Power, Body and Conscience - Josip Bošnjaković (Nova Prisutnost, 2022)
The wounds on the Body of Christ are a part of God’s identity. Pierced arms, hips, and legs are a sign and testimony of the Paschal Mystery that is Passion, Death, and Resurrection. The Church is a vulnerable and wounded Body, just as any other person is vulnerable and wounded. The Body of the Church and the body of a person can be wounded by processes that take place within the Body/bodies, and other institutions, persons, states, Churches, religions. The article discusses the wounding of the Church due to the consequences of the processes that take place within the body, and above all, due to the abuse of power, body, and conscience. When the body is exposed to the gaze of others due to being wounded, then a reaction is possible through the feeling of shame, through a complex experience that speaks of the inner process of a being that feels ashamed, which is exposed to the gaze of others. Recovery from wounding is a lengthy process that requires openness, honesty, wound detection, and talking about the course of events that led to wounding. At the same time, the wounded Body needs help, hence the article talks about possible recovery from abuse through tenderness, compassion, empathy, spiritual monitoring of people on their path to recovery.